Trail of tears a Native American documentary collection. - Richie, Chip.; Heape, Steven R.; Studi, Wes.; Jones, James Earl.; Howard, Gregg; Ross, Gayle; Mill Creek Entertainment ([United States] : Mill Creek Entertainment, 2009)
Trail of tears : Cherokee legacy: Documents the forced removal in 1838 of the Cherokee Nation from the southeastern United States to Oklahoma. Shows the suffering endured by the Cherokees as they lost their land and the difficult conditions they endured on the trail. Describes how thousands of Cherokees died during the Trail of Tears, nearly a quarter of the nation, including most of their children and elders.
Black Indians: Explores issues of racial identity between the mixed-descent peoples of both Native American and African American heritage. James Earl Jones is himself a Black Indian.
Native American healing in the 21st century: Learn from today's respected physicians the crossover of ancient native remedies to present-day medical practices. Explore for healing plants and herbs. Learn from tribal elders traditional healing practices and philosophies. Discover the contents of a recently found 350-year-old medicine bag. Compare the similarities of Native American and Chinese healing.
Our spirits don't speak English: Imagine you are a child, taken from your home, your family, taken from everything you know. In 1869, the U.S. government enacted a policy of educating Native American children in the ways of western society. By the late 1960's, more than 100,000 had been forced to attend Indian Boarding School.
Disc 1. Trail of tears : Cherokee legacy (105 min.) -- Disc 2. Black Indians : an American story (52 min.) ; Native American healing in the 21st century (52 min.) ; Our spirits don't speak English : Indian boarding school (53 min.).
Originally released separately: 2006, 2001, 2004, and 2008.
Trail of tears : Cherokee legacy: written by Daniel Blake Smith ; produced by Chip Richie and Steven R. Heape ; directed by Chip Richie.
Black Indians: written by Daniel Blake Smith ; directed by Chip Richie.
Native American healing in the 21st century: written by Howard Fisher ; produced and directed by Chip Richie.
Our spirits don't speak English: written by Dan Agent ; directed by Chip Richie.
Trail of tears : Cherokee legacy: narrator, James Earl Jones ; host, Wes Studi ; celebrity voices, James Garner, Crystal Gayle, John Buttrum, Douglas Wilder.
Keywords: Trail of Tears, 1838-1839.; Cherokee Indians -- Relocation; Cherokee Indians -- History -- 19th century; Cherokee Indians -- Government relations; Indians, Treatment of -- United States -- History -- 19th century; African Americans -- Relations with Indians; Indians of North America -- Mixed descent; Indians of North America -- Medicine; Indians of North America -- Ethnobotany; Medicinal plants -- North America; Indians of North America -- Education -- History; Off-reservation boarding schools -- United States; Indian students -- United States -- History; Discrimination in education -- United States -- History; Documentary films